Pronatal Property Rights over Land and Fertility Outcomes Evidence from a Natural Experiment in Ethiopia - Ali, Daniel Ayalew (World Bank E-Library Archive, 2015)
This study exploits a natural experiment to investigate the impact of land reform on the fertility outcomes of households in rural Ethiopia. Public policies and customs created a situation where Ethiopian households could influence their usufruct rights to land via a demographic expansion of the family. The study evaluates the impact of the abolishment of these pronatal property rights on fertility outcomes. By matching aggregated census data before and after the reform with administrative data on the reform, a difference-in-differences approach between reform and non-reform districts is used to assess the impact of the reform on fertility outcomes. The impact appears to be large. The study estimates that women in rural areas reduced their life-time fertility by 1.2 children due to the reform. Robustness checks show that the impact estimates are not biased by spillovers or policy endogeneity